Angiographic CT: in vitro comparison of different carotid artery stents using two different angiography systems - Lettau, Michael; Bendszus, Martin; Hähnel, Stefan (Journal of neuroradiology, 2013)
Background and purpose: Our aim was to evaluate the in vitro visualization of different carotid artery stents on Angiographic CT (ACT). Of particular interest was the measurement of artificial lumen narrowing (ALN) caused by the stent material within the stented vessel segment to determine whether ACT can be used to detect restenosis within the stent. Material and methods: ACT appearances of 17 carotid artery stents of different designs and sizes (4.0 to 11.0 mm) were investigated in vitro. All stents were imaged on two different angiography systems. For each stent, artificial lumen narrowing (ALN) was calculated. Results: The ALN on the two different angiography systems did not significantly differ. With standard algorithm image reconstruction, ALN ranged from 19.1 to 46.6%. With stent-optimized algorithm image reconstruction, ALN was significantly lower and ranged from 7.6 to 17.2%. Different stents showed significantly different degree of ALN. Stent struts could be visualized in all stents. Conclusion: In our in vitro model, ACT evaluation of vessel patency after stent placement is possible but is impaired by ALN. Stent-optimized algorithm image reconstruction decreases ALN but further research is required to define the visibility of in-stent stenosis depending on image reconstruction.
Gesehen am 27.01.2022